Digital Teaching Materials for Explanatory Texts to Strengthen Critical Thinking for High School Students - Purwaningsih, Tri Wahyuni; Rozak, Abdul; Wiradinata, Rochanda (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to develop digital teaching materials for explanatory texts to strengthen high school students' critical thinking. Formulation of the problem of this research (1) How do digital explanatory text teaching materials strengthen critical thinking? (2) What are the results of implementing digital explanatory text teaching materials to strengthen critical thinking? This research uses research and development methods with the ADDIE model. The steps in this research consist of needs analysis, designing digital teaching materials, developing digital teaching materials, implementing digital teaching material products, and evaluating digital teaching material products. The method for collecting data in this research is by collecting data from the results of expert validation questionnaires and student assessment questionnaires. The data obtained was analyzed descriptively using a Likert scale. The results of the design of digital teaching materials for explanatory texts to strengthen high school students' critical thinking consist of cover, material, post-material, Canva video, and accompanied by musical instruments that can be accessed using a computer or smartphone. The results of product assessments by validity experts (materials, media and teachers) as well as the results of student questionnaires regarding digital teaching material products with explanatory texts are stated in the "feasible" category. Test results in the implementation of explanatory text digital teaching materials to strengthen students' critical thinking at MA Al-Zaytun and SMAN 1 Gantar, the average student score has increased compared to before implementing explanatory text digital teaching materials. The conclusion of this research is that the results of tests and questionnaires on digital teaching materials for explanatory texts to strengthen high school students' critical thinking are categorized as having improved. The respondents' assessment indicates that the digital teaching material product, explanatory text for enhancing high school students' critical thinking, meets the necessary criteria for use by students or teachers.